Effects of lysine vasopressin and glypressin on the fibrinolytic system in cirrhosis. Issue 7 (July 1979) - Douglas, J G; Forrest, J A; Prowse, C V; Cash, J D; Finlayson, N D
Abstract : In eight patients with cirrhosis of the liver and portal hypertension an intravenous infusion of lysine vasopressin induced a rapid increase in the plasma level of the fibrinolytic proenzyme plasminogen activator. In contrast, triglycyl lysine vasopressin (glypressin; GVP), in a dose known to lower portal venous pressure, produced no fibrinolytic response. This lack of fibrinolytic response represents an advantage of GVP over lysine vasopressin in addition to its longer in vivo half-life and lower cardiotoxicity. Clinical trials of GVP in the treatment of bleeding oesophageal varices are needed.